Analysis of Drug Availability Management at the Regional General Hospital Pharmacy Installation - Sani, Hapiz Arlanda; Asriwati, Asriwati; Nyorong, Mappeaty; Sari, Mayang; Ginting, Indra (Journal La Medihealtico, 2023)
Pharmacy managerial activities are inseparable from the principles of drug availability management such as a series of needs planning activities, procurement, storage and distribution of drugs through hospital pharmacy installations. This study aims to analyze and obtain information on availability management at the Pharmacy Installation of the South Tapanuli Regional General Hospital. This type of research is qualitative with a descriptive approach using primary data and secondary data using the interview method. The informants interviewed at the pharmaceutical installation were the head of the pharmaceutical installation unit, the coordinator of pharmacy services, the head of the pharmaceutical warehouse/supplies, the coordinator of quality management and administration. Informants of this study were taken by purposive sampling and data analysis using triangulation and data reduction methods. The results of this study obtained that planning for drug needs uses the consumption method by looking at the need for previous use, but it has not been maximized, procurement has not gone well, drug shortages often occur, drug storage systems use the FIFO (First in First Out) and FEFO (First Expired First Out) systems. First Expired First Out). Storage is not up to standard, the waiting time for drug distribution to patients starting from the patient submitting the prescription to the delivery of the drug takes quite a long time for the drug to be finished. The conclusion is that the implementation of drug availability management has not run optimally according to standard operating procedures for services, so it is necessary to increase human resource knowledge through training related to drug planning.